The Role of The Principal in Developing The Islamic Attitude Program for Children with Special Needs at SLB Negeri Aceh Jaya - Nurbayani Ali; Fauziah Fauziah; Maimun Sari (Ar-Raniry: International Journal of Islamic Studies, 2022)
Improving the quality of education in schools has a major effect on the leadership of the principal. As it is known that the principal has an important task in directing all existing school personnel, so that they can work together in achieving school goals. This study aims to find out how the role and obstacles of the principal in developing an Islamic attitude program for children with special needs in SLB Negeri Aceh Jaya. This research method is in the form of qualitative research. Subjects in this study consisted of principals and teachers. Data collection techniques consist of observation, interviews, and documentation. Data analysis techniques consist of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the principal's role as a leader in SLB Aceh Jaya has so far implemented several programs in learning activities. One of the principal's programs in developing Islamic attitudes in students. This Islamic attitude aims to teach students about manners, mutual respect, mutual respect, and teaches students to always read prayers first before carrying out activities. This Islamic attitude program also requires cooperation between school principals, school committees, teachers, and parents. The goal is to instill Islamic values in students.